Kemampuan Membaca Al-Qur'an Pendidik Agama Islam: Tracer Alumni PTKI Jakarta Banten - Lamya Hayatina; Ika Ika (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Competence in reading the Qur’an is a foundational aspect of the credibility and professionalism of Islamic Religious Education (PAI) teachers. However, understanding the actual level of competence, the challenges faced, and the need for professional development among PAI teachers who graduated from Islamic Higher Education Institutions (PTKI) requires further in-depth investigation to design effective and sustainable development programs. This study employed a qualitative phenomenological approach. Data were collected through focus group discussion (FGD) interviews with leaders and lecturers of Islamic Higher Education Institutions (PTKI) in the Jakarta–Banten region, as well as online questionnaires administered to 21 Islamic Religious Education (PAI) teachers who are alumni of various PTKI. The instrument assessed Qur’an reading competence (covering aspects of makhraj, ṣifāt al-ḥurūf, tajwīd, and fluency), practice frequency, challenges, and their needs for further training. The collected data were analyzed descriptively to map current conditions and emerging trends. The findings reveal that although most teachers read the Qur’an daily and assess their competence at a moderate to good level, they face key challenges such as limited time (42.9%), limited access to qualified mentors (19%), and low self-motivation (9.5%). All respondents (100%) expressed a need for further training, with 81% indicating a strong need. Regarding preferred training models, periodic intensive workshops (23.8%) and blended learning approaches (42.9%) were the most favored, supported by digital features such as AI-based practice tools (19%) and interactive video tutorials (38.1%). These findings imply that PTKI, as the alumni’s parent institution, should develop strategic, technology-based, and community-oriented continuous training programs to enhance the quality of PAI teachers.